OPTIMIZING CRIMINAL IMMIGRATION LAW ENFORCEMENT AGAINST INDONESIAN CITIZENS PROVIDING FALSE INFORMATION DURING INTERNATIONAL DEPARTURE PROCEDURES: A STUDY AT BATAM PORT - Irpan Husein; Erniyanti; Agus Siagian; Markus Gunawan (PT. Radja Intercontinental Publishing, 2026)
The departure of Indonesian citizens (WNI) abroad through Batam Port must comply with immigration regulations, including the obligation to provide truthful information during the immigration inspection process. Law Number 6 of 2011 concerning Immigration, as amended several times, most recently by Law Number 63 of 2024, as well as Law Number 1 of 2023 concerning the Criminal Code and implementing regulations in the field of immigration, constitutes the legal framework for this research. Providing false information during the departure process may hinder the implementation of immigration supervision and, if the elements of a criminal offense are fulfilled, may result in criminal liability. This research aims to analyze the legal regulation, implementation, obstacles, and solutions related to criminal immigration law enforcement. This research analyzes several legal theories based on the views of legal scholars. It employs an empirical legal research method using statutory, conceptual, and sociological approaches. Data were obtained through literature studies and field research concerning the implementation of immigration inspection and supervision. The data were analyzed qualitatively to determine the conformity between statutory provisions and the practice of law enforcement at Batam Port. The results show that law enforcement against Indonesian citizens who provide false information is based on immigration and criminal law provisions, subject to the fulfillment of the elements of a criminal offense. The implementation of law enforcement at Batam Port is conducted through the examination of travel documents, identity, purpose of departure, and clarification of inconsistent information. The obstacles identified include difficulties in proving the element of intent, limitations and suboptimal integration of data, differences in understanding in determining the legal qualification of the conduct, and inadequate coordination among relevant agencies. This research concludes that criminal immigration law enforcement has a legal basis; however, its implementation still requires optimization in the aspects of inspection, evidence, data integration, and inter-agency coordination. Law enforcement must be conducted based on the fulfillment of the elements of a criminal offense while maintaining a distinction between administrative violations and criminal offenses. Optimization is necessary to achieve effective and proportionate law enforcement, provide legal certainty, and strengthen the function of immigration supervision in the process of Indonesian citizens leaving abroad.